Efektivitas Pelatihan Konselor Sebaya Terhadap Keterampilan Skrining Masalah Kesehatan Mental Pada Mahasiswa University Residence (Unires) - Lukman Al Hakim; Warih Andan Puspitosori (Malahayati Nursing Journal, 2025)
ABSTRACT Students who live in dormitories are a vulnerable group experiencing mental health problems due to academic pressure and social adaptation challenges. Stigma and a lack of knowledge often act as barriers to seeking professional help. Peer counselor programs have emerged as a strategic solution for early detection, yet the effectiveness of their training in equipping screening skills requires evaluation. This study aimed to determine the effectiveness of peer counselor training in enhancing mental health problem screening skills (knowledge, attitude, and experience) among students of the University Residence (Unires). This study employed a quasi-experimental design with a pre-test and post-test approach. The sample consisted of 43 Unires residents selected through consecutive sampling. The intervention was a structured peer counselor training program. Data were collected using a questionnaire before and after the intervention and analyzed using the non-parametric Wilcoxon Signed-Rank Test. The analysis revealed a statistically significant increase in the mean scores for knowledge (p0.05) and experience (p0.05) following the training. The mean knowledge score increased from 3.48 to 4.09, while the mean experience score rose from 2.18 to 3.39. However, no significant change was found in the attitude scores of the respondents (p0.05). The peer counselor training proved to be partially effective in enhancing conceptual understanding (knowledge) and practical capabilities (experience), but was not potent enough to significantly alter their affective disposition (attitude). Keywords: Peer Counselor, Mental Health, Screening Skills, Training.  ABSTRAK Mahasiswa yang tinggal di asrama merupakan kelompok rentan mengalami masalah kesehatan mental akibat tekanan akademik dan tantangan adaptasi sosial. Stigma dan kurangnya pengetahuan seringkali menjadi penghalang untuk mencari bantuan profesional. Program konselor sebaya menjadi solusi strategis untuk deteksi dini, namun efektivitas pelatihannya dalam membekali keterampilan skrining perlu dievaluasi. Penelitian ini bertujuan mengetahui efektivitas pelatihan konselor sebaya terhadap peningkatan keterampilan skrining masalah kesehatan mental (pengetahuan, sikap, dan pengalaman) pada mahasiswa Asrama University Residence (Unires). Penelitian ini menggunakan desain kuasi-eksperimental dengan pendekatan pre-test and post-test design. Sampel terdiri dari 43 mahasiswa penghuni Unires yang dipilih melalui consecutive sampling. Intervensi berupa program pelatihan konselor sebaya yang terstruktur. Data dikumpulkan menggunakan kuesioner sebelum dan sesudah intervensi, lalu dianalisis menggunakan uji non-parametrik Wilcoxon Signed-Rank Test. Hasil analisis menunjukkan adanya peningkatan yang signifikan secara statistik pada skor rata-rata pengetahuan (p0,05) dan pengalaman (p0,05) setelah pelatihan. Skor rata-rata pengetahuan meningkat dari 3,48 menjadi 4,09, sementara skor pengalaman meningkat dari 2,18 menjadi 3,39. Namun, tidak ditemukan perubahan yang signifikan pada skor sikap responden (p0,05). Pelatihan konselor sebaya terbukti efektif secara parsial dalam meningkatkan pemahaman konseptual (pengetahuan) dan kapabilitas praktis (pengalaman), namun belum cukup kuat untuk mengubah disposisi afektif (sikap) secara signifikan. Kata Kunci: Konselor Sebaya, Kesehatan Mental, Keterampilan Skrining, Pelatihan.